2005
DOI: 10.1016/j.neuron.2005.02.011
|View full text |Cite
|
Sign up to set email alerts
|

mGluR7 Is a Metaplastic Switch Controlling Bidirectional Plasticity of Feedforward Inhibition

Abstract: Plasticity of feedforward inhibition in the hippocampal mossy fiber (MF) pathway can dramatically influence dentate gyrus-CA3 dialog. Interestingly, MF inputs to CA3 stratum lucidum interneurons (SLINs) undergo long-term depression (LTD) following high-frequency stimulation (HFS), in contrast to MF-pyramid (PYR) synapses, where long-term potentiation (LTP) occurs. Furthermore, activity-induced potentiation of MF-SLIN transmission has not previously been observed. Here we report that metabotropic glutamate rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
226
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(236 citation statements)
references
References 53 publications
(3 reference statements)
9
226
0
1
Order By: Relevance
“…Two avenues of investigation allowed us to reach this conclusion. First, using overexpression of a myc-tagged mGluR7 in cultured hippocampal neurons, we demonstrated that the same duration application of L-AP4 resulted in a robust internalization of both isoforms of mGluR7a and b (Pelkey et al, 2005). This observation was then extended to immunoelectron microscopy of mossy fiber filopodial terminals.…”
Section: Mglur7 Functions As a Trigger For Bidirectional Plasticity Amentioning
confidence: 81%
See 2 more Smart Citations
“…Two avenues of investigation allowed us to reach this conclusion. First, using overexpression of a myc-tagged mGluR7 in cultured hippocampal neurons, we demonstrated that the same duration application of L-AP4 resulted in a robust internalization of both isoforms of mGluR7a and b (Pelkey et al, 2005). This observation was then extended to immunoelectron microscopy of mossy fiber filopodial terminals.…”
Section: Mglur7 Functions As a Trigger For Bidirectional Plasticity Amentioning
confidence: 81%
“…In marked contrast, the same high-frequency induction protocol that causes LTP at principal cell synapses induces two distinct forms of long-term depression (LTD) at mossy fiber-interneuron synapses (Figs. 4 and 5) (Maccaferri et al, 1998;Lei and McBain, 2004;Pelkey et al, 2005). One can immediately appreciate that this differential, strengthening of synapses onto CA3 pyramidal cells combined with a simultaneous weakening of transmission onto stratum lucidum interneurons will have important consequences for the dynamics of the CA3 circuit.…”
Section: Mossy Fiber-inhibitory Interneuron Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been recently shown that AMN082 and other mGluRselective agonists facilitate mGluR7 receptor internalization 52,53 in addition to stimulating the receptor. This could induce a functional blockade of mGluR7 subsequent to its activation.…”
Section: Mglur7 Downregulation Blocks Extinction Of Conditioned Fearmentioning
confidence: 99%
“…In CA3 pyramidal neurons, highfrequency stimulation (HFS) leads to a large posttetanic potentiation (∼800%) and long-term potentiation (∼200%; [36,68,71,88,89]). In contrast, in stratum lucidum interneurons HFS induces synaptic depression rather than potentiation [50,67]. Likewise, activation of the cAMP pathway by forskolin leads to a large chemical potentiation at mossy fiber-CA3 pyramidal neuron synapses [45,82], but has only minimal effects on monosynaptic transmission at mossy fiber-stratum lucidum interneurons [55].…”
Section: Differential Synaptic Transmission At Mossy Fiber-pyramidal mentioning
confidence: 99%